Impact evaluation of a fisheries development project. (November 2017) - Chu, Jingjie; Garlock, Taryn M.; Sayon, Patrick; Asche, Frank; Anderson, James L.
Abstract: A number of fisheries development projects are undertaken every year in recognition of the important role fisheries play in many coastal communities. The objectives vary, but typically go beyond a limited focus on fisheries management and the ecosystem. This makes it difficult to evaluate the contribution of a project, particularly in data poor environments such as most developing countries. This paper used the recently developed Fisheries Performance Indicators (FPIs) to evaluate the impact of a World Bank development project in a Liberian coastal community. FPIs are designed to capture economic and social performance of a fisheries system in addition to the management and environmental impacts. The results show improvements in most ecological dimensions, and also in many social and economic dimensions targeted by the project. Hence, the project intervention appears to be positive. However, some indicators, particularly in relation to general governance in Liberia, showed a negative development which was not caused by the project.